THE GOVERNMENT'S ROLE IN IMPROVING THE QUALITY OF MSME PRODUCTS IN SEPANDE VILLAGE - Aurandhi Sp , Alnesta; Rodiyah, Isnaini (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze and describe the role of the government in improving the quality of MSME products in Sepande village. Method: The research method used uses a qualitative method. This research was carried out in Sepande Village, Sidoarjo District, Sidoarjo Regency. The focus of the research is to analyze the role of the government, this role is divided into 5 indicators, namely l) Regulator, 2) Facilitator, 3) Dynamizer, 4) Protector, 5) Promoter. Data collection techniques use interviews, observation and documentation, data analysis using qualitative descriptive analysis. Results: The results of the study concluded that the Government of Sidoarjo Regency and Sepande Village has tried to carry out its role as regulators, facilitators, dynamizers, protectors, and promoters through various programs such as